PERANCANGAN JALUR SALURAN DRAINASE GUNA MENANGGULANGI BANJIR PADA PERUMAHAN WARGA - Reza Gibran; Syaiful Syaiful; Rulhendri Rulhendri (JPMUJ, 2024)
In the area of Jl. RE. Soemantadiredja No.351, Palasari, Kec. Cijeruk, Bogor Regency, West Java, drainage channel is a water outlet that is located below or above the surface naturally or artificially. This housing does not have a water outlet, so when it rains the moving water cannot pass and causes flooding in the area, because the water discharge is getting higher, the existing wall between community settlements & housing collapses leads to community settlements, agricultural land, and livestock. Public. After carrying out site management, we found a solution to the flood problem by making a drainage link for flood water disposal that leads to the pond, to prevent landslides in the community's rice fields, it is necessary to build water channels made of materials in line with the emergency artificial river channels made by society.